2009
DOI: 10.1359/jbmr.080907
|View full text |Cite
|
Sign up to set email alerts
|

Paget's Disease of Bone: Histologic Analysis of 754 Patients

Abstract: Although Paget's disease of bone (PDB) is the second most common metabolic bone disease, to our knowledge, there is only one quantitative analysis on the histological and especially on the histomorphometric level. Therefore, the aim of this study was to analyze, on the basis of the Hamburg Bone Register, PBD in terms of incidence, skeletal distribution, malignant transformation, and histological and histomorphometric characteristics. Bone biopsies and patient files of 754 cases with histologically proven PDB w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 32 publications
5
71
0
1
Order By: Relevance
“…70,71 Paget's disease affects localized skeletal sites, most often the pelvis, spine, femur or tibia. 70,71 The disease is most often diagnosed through X-rays, by the bone's strikingly high increase in bone volume due to high levels of bone turnover. 71 Individuals with Paget's disease commonly suffer from bone enlargement, bowing/deformity and pain.…”
Section: Paget's Disease Of Bone (Pdb)mentioning
confidence: 99%
See 1 more Smart Citation
“…70,71 Paget's disease affects localized skeletal sites, most often the pelvis, spine, femur or tibia. 70,71 The disease is most often diagnosed through X-rays, by the bone's strikingly high increase in bone volume due to high levels of bone turnover. 71 Individuals with Paget's disease commonly suffer from bone enlargement, bowing/deformity and pain.…”
Section: Paget's Disease Of Bone (Pdb)mentioning
confidence: 99%
“…70,71 The disease is most often diagnosed through X-rays, by the bone's strikingly high increase in bone volume due to high levels of bone turnover. 71 Individuals with Paget's disease commonly suffer from bone enlargement, bowing/deformity and pain. Incomplete fractures, The fracture mechanics of human bone EA Zimmermann et al termed pseudo or fissure fractures, can be found at sites with severe bowing and deformity.…”
Section: Paget's Disease Of Bone (Pdb)mentioning
confidence: 99%
“…The spine has been reported to be the second most commonly affected site in Paget disease of bone (PDB), a chronic metabolically active bone disease [1][2][3][4][5][6][7]. Monostotic pagetic involvement of the spine is rarely described, and polyostotic cases are more common [8].…”
Section: Introductionmentioning
confidence: 99%
“…In this particular case, it was probably performed to exclude the possibility of a chronic osteomyelitis. The typical histology of PDB lesions shows increased osteoclasts, which are often enlarged and multinucleated, and disorganised woven bone (2,3). In our case, the findings of the biopsy were consistent with the these features.…”
Section: N Discussionmentioning
confidence: 99%
“…It is hypothesized that the primary abnormality might be an increased osteoclast activity. Osteoclasts prove to be enlarged in size and high in number (2). The newly formed bone is irregular, lacking the normal lamellar pattern and increased in volume, sclerotic and weaker than normal bone.…”
mentioning
confidence: 99%